Law of the sea in dialogue - Hestermeyer, Holger; Matz-Lück, Nele; Seibert-Fohr, Anja; Vöneky, Silja; SpringerLink (Online service). (Berlin New York Springer, 2011)
The interrelation between different fields of public international law has particular relevance for the systematic understanding of international law. The book contains a collection of essays on the law of the sea and its interdependencies with other current legal issues of global importance. The issue of the relationship between global warming and law of the sea matters are one focus. In a second thematic section the collection addresses the global commons. The third part deals with security issues. The recent increase in piracy activities has shown the relevance of discussing the linkage between the law of the sea and security issues
Part 1: Global warming Global warming and state responsibility Measures to fight climate change A role for the law of the sea? An agreement in principle? The Copenhagen Accord and the post-2012 climate regime The reluctance of the United States to ratify treaties Part 2: Exploitation and the use of the global commons The division of the commons? The myth of the commons: divide or perish Judicial action for the common heritage Part 3: Law of the sea and security East African piracy and the defense of world public order Piracy at sea, a new approach to an old menace The Security Council and the security on the seas
Includes bibliographical references
Electronic reproduction
Keywords: Law of the sea